Water table contribution to alfalfa water use in different environments of the Argentine Pampas - Dardanelli, Julio Luis (2002)
In the Argentine Pampas, although the water table is considered an important source of water supply for the alfalfa crop, it has not been previously quantified.The goal of this study was to estimate the water table contribution to alfalfa water use in several environments, using an indirect method derived from water use efficiency determinations. Data sets were obtained from experiments conducted for four growing seasons at four locations: Anguil, Rafaela, General Villegas and Manfredi. Water table contribution was estimated considering the crop water use efficiency and the water use from the upper layers (rainfall supplied). Capillary contribution from the water table was assumed, if the dry matter/water use from the upper layers ratio was higher than a given water use efficiency threshold. When present, the water table contribution varied among locations between 15 and 25% of the crop water use, and was not related to the groundwater depth. A pooled exponential relationship between the seasonal water table contribution and seasonal effective rainfall was determined.